INCREASING STUDENT LEARNING MOTIVATION IN JUNIOR HIGH SCHOOL STUDENTS THROUGH COLLABORATIVE LEARNING METHODS - Malay, Irvan; Sihotang, Silverius Yoan; Sembiring, Tuahta; Febriansyah, Dio Ananda; Khairunisa, Vira (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Most of the learning processes that take place in elementary schools, on the one hand, are still dominated by the role of the teacher, but also have a negative impact, namely the lack of active participation of students in learning activities. One of them is the lack of diversity in the strategies and methods used by teachers in carrying out their learning. The learning process in elementary school is relatively passive, the teacher explains the material, and students sit and listen, recite, and recite, this is what is called teacher-centered learning. The learning-by-doing learning model is the concept of learning while working and working actively. The pragmatic view of education is mainly based on two reasons: one is destiny, children are an active existence, and the other is that students need to impulsively participate in the learning process through children's work.